(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents scientific information on soybean plant characteristics, morphology, anatomy, biological classification, cultivation, and the work that should be done to increase its importance and productivity in agriculture.